Urinary sodium and iodine concentrations among Belgian adults: results from the first national Health Examination Survey - Vandevijvere, Stefanie; Ruttens, Ann; Wilmet, Alain; Marien, Cédric; Hautekiet, Pauline; Van Loco, Joris; Moreno-Reyes, Rodrigo; Van der Heyden, Johan (European journal of clinical nutrition, 2021)
Iodine deficiency and excessive salt intakes have adverse health consequences. The objective was to measure sodium and iodine concentrations in urine spot samples among a representative sample of Belgian adults and compare those to World Health Organization (WHO) recommendations. Spot urine samples were collected in 2018 from participants of the Belgian Health Examination Survey. Iodine and sodium concentrations were measured by inductively coupled plasma mass spectrometry and ion selective electrodes respectively. Tanaka and INTERSALT equations were used to predict 24-h urinary sodium excretion using sodium and creatinine concentration in spot samples, sex, and measured height and weight. Median urinary iodine concentration (UIC) among adults (n = 1092) was 93.6 µg/L, indicating mild iodine deficiency according to WHO thresholds. Median UIC among participants who reported thyroid problems over the last year was significantly higher than among those who did not report thyroid problems (104.1 µg/L versus UIC = 92.2 µg/L, p < 0.001). There were no significant differences in median UIC between sexes, age groups, and regions. The average salt intake among Belgian adults (n = 1120) was 8.3 ± 0.1 g/day using the Tanaka equation and 9.4 ± 0.1 g/day using the INTERSALT equation. For both equations, <5% of the population met the recommended WHO upper salt intake level of 5 g/day. Iodine nutrition in the Belgian adult, nonpregnant population likely indicates mild iodine deficiency as the median UIC was below the WHO threshold for iodine sufficiency. Salt intake was substantially higher than the WHO recommendations. Further policy efforts are needed to optimize iodine and reduce salt intake in Belgium.